Tumor microenvironment-modulating oncolytic adenovirus combined with GSK-3β inhibitor enhances antitumor immune response against bladder cancer - Yoon, A-Rum; Jiao, Ao; Hong, JinWoo; Kim, Bomi; Yun, Chae-Ok (Frontiers in Immunology, 2024)
Bladder cancer is a common type of cancer around the world, and majority of the patients are diagnosed with non-muscle-invasive bladder cancer (NMIBC). Although low-risk NMIBC have good prognosis, disease recurrence rate and development of treatment refractory disease remains high in intermediate to high risk NMIBC patients. To address these challenges for the treatment of NMIBC, a novel combination therapy composed of an oncolytic adenovirus (oAd) co-expressing interleukin (IL)-12 (IL12), granulocytemacrophage colony-stimulating factor (GMCSF), and relaxin (RLX; HY-oAd) and a clinical stage glycogen synthase kinase (GSK)-3β inhibitor (9-ING-41; elraglusib) was investigated in the present report. Our findings demonstrate that HY-oAd and iGSK3β 9-ING-41 combination therapy (HY-oAd+9-ING-41) exerted superior inhibition of tumor growth compared with respective monotherapy in a syngeneic NMIBC tumor model. HY-oAd+9-ING-41induced high level tumor extracellular matrix (ECM) degradation and more potent antitumor immune response than the respective monotherapy. In detail, HY-oAd+9-ING-41 induced superior accumulation of intratumoral T cells, prevention of immune cell exhaustion, and induction of tumor-specific adaptive immune response than either monotherapy. Collectively, these results demonstrate that the combination of HY-oAd and 9-ING-41 may be a promising approach to elicit a potent antitumor immune response against bladder cancer.